Exploring concerns in the implementation of green accounting: A case study on MSMEs Batik Business - Chamalinda Khy’sh Nusri Leapatra; Kusufi Muhammad Syam; Sari Silli Sartika; Jamilah Imratul; Damayanti Wilda Sophie (BIO Web of Conferences)
Green accounting, also known as environmental accounting, focuses on a more comprehensive view of an organisation's financial performance by taking into account environmental impacts. The batik business has a considerable influence on the preservation of nature due to several factors related to the production process and the raw materials used.This research was conducted on MSMEs batik business in the Madura region. This type of business was chosen because this type of business has a considerable influence on natural sustainability. This research explores the extent to which business people as one of the main elements care about the environment and know and have knowledge about green accounting. This research uses a qualitative method with a case study approach. Data collection techniques are observation, interview, and documentation. Data analysis was carried out with the stages of data reduction, data presentation, and conclusion drawing. The results of the study state that batik business actors in the Madura region have a good understanding and concern for protecting their business environment as a form of green accounting implementation. This understanding is evidenced by how business actors understand and allocate business costs and environmental costs, and separate personal funds from business funds. Although their understanding of specific business and environmental costs is limited, they already understand that environmental costs are costs charged to their business as a form of responsibility. The implications of this research are expected to be useful in realising optimal green accounting practices, not only for batik business MSMEs but also for business actors in other business fields.